2011
DOI: 10.1179/2047773211y.0000000015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effectiveness and compliance of intermittent preventive treatment (IPT) in the control of malaria in pregnant women in south eastern Nigeria

Abstract: Controlling malaria in pregnancy has been an important component of the millennium development goal and intermittent preventive treatment (IPT) is considered an important tool in controlling malaria among pregnant women. In this study, we evaluated the level of compliance to IPT use as well as its effect on malaria infection among pregnant women attending antenatal clinic in south eastern Nigeria. Peripheral blood smears and placental histology were used as diagnostic tools to determine infection rate. Our dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…This situation is aggravated by low ITN use, as observed in other centers. 19 Akinleye et al 18 reported increasing uptake of IPTp with increasing parity (up to the third pregnancy), but no association between IPTp uptake and respondent age. In this study, however, we found that older maternal age ( §20 years), multiparity, secondary school or higher level of education, and ITN use were associated with greater adherence to IPTp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This situation is aggravated by low ITN use, as observed in other centers. 19 Akinleye et al 18 reported increasing uptake of IPTp with increasing parity (up to the third pregnancy), but no association between IPTp uptake and respondent age. In this study, however, we found that older maternal age ( §20 years), multiparity, secondary school or higher level of education, and ITN use were associated with greater adherence to IPTp.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Facilitybased studies in other African countries reported adherence rates of 52.3 and 32% in Uganda and the Gambia, respectively. 27,28 Compared to roll back malaria coverage target of 80% for 2010, countrywide surveys in Africa have shown IPTp two dose coverage ranging from as low as 1% in Benin republic to 70% in Zambia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 In this study, between 25% to 41% of pregnant women received two doses of IPTp with SP. Similar studies conducted in South East 42 , South West [43][44][45] , North East 46 and at the national level in Nigeria 47 showed that about 37% of pregnant women received two doses of IPTp less than the target of RBM program indicating low adherence and uptake of IPTp for patients who sought care at health facilities. A study conducted in Uganda also show that only about a quarter of pregnant women receive two doses of IPTp with SP.…”
Section: Discussionmentioning
confidence: 65%
“…Age below 20 years, lack of formal education, rural life and parity superior to one were also identified as negative influences on IPTp-SP adherence. On the other hand, a study carried out in Nigeria in 2010 showed that the primiparae adhered better to the IPTp-SP compared to the secondipares and the multipares [14]. In Uganda between 2008 and 2009, a cross-sectional study on 500 women who were pregnant the previous year revealed that women were more likely to observe IPTp-SP if administered during the prenatal consultation [26].…”
Section: Discussionmentioning
confidence: 99%